Influence of Guidelines in the «Programa de Segregación en la Fuente y Recolección Selectiva de Residuos Sólidos» in the Municipality of San Martin De Porres and Ate, Peru (2011-2017) - Gallegos Blas, Keth Lee Jacob (2020)
The objective of the research was to analyze the influence of the guidelines in the «Programa de Segregación en la Fuente y Recolección Selectiva» of the districts of San Martin de Porres and Ate; as well as, the comparison of the evolution of each segregation program from 2011 to 2017, using a descriptive approach. The research presented the description of the current situation of the use of solid waste in Peru, the manifestation of recycling at lawful devices, and the description of each segregation program of both districts. Likewise, the research analyzed the amount of solid waste collected, management conventions, and the valuation of environmental benefits in kg of CO2 avoided from both segregation programs. In conclusion, in 2017 Ate presented a bigger amount of solid waste collected than San Martín de Porres, it was a different of 254,4 tons. Also, Ate presented three more management conventions than San Martín de Porres, which represent an advantage in order to acquire greater benefits for its program. In terms of valuation of environmental benefits, Ate exceeded by 400.543 kg of CO2 to San Martín de Porres. The great results of the three guidelines analyzed led Ate to present itself as an exemplary municipality with a program that has a strategic base, with a view to sustainability.